Crucial conversations : tools for talking when stakes are high - Patterson, Kerry, 1946- (New York : McGraw-Hill, 2012)
From the Dust Jacket: Perhaps once a decade, a book comes along that transforms people's lives in a very real, measurable way. This is one of them. Crucial Conversations exploded onto the scene ten years ago and revolutionized the way people communicate when stakes are high, opinions vary, and emotions run strong. Since then, millions of people have learned how to hold effective crucial conversations and have dramatically improved their lives and careers thanks to the methods outlined in this book. Now, the authors have revised their bestselling classic to provide even more ways to help you take the lead in any tough conversation: New firsthand accounts of how these skills changed readers' lives; New case studies showing how business leaders successfully applied these methods to achieve results; New links to videos teaching what to do and what to avoid during crucial conservations; New research findings offering fresh insights for applying the skills taught in the book. Crucial Conservations is filled with practical advice you can start using today: Prepare for high-stakes conservations; Make it safe to talk about almost anything; Transform unpleasant emotions into powerful dialogue; Be persuasive, not abrasive. Crucial Conservations gets you past the hard parts of dialogue and helps you achieve relationships that are real, productive, and that will enrich your life and career.
What's a crucial conversation? : and who cares? -- Mastering crucial conversations : the power of dialogue -- Start with heart : how to stay focused on what you really want -- Learn to look : how to notice when safety is at risk -- Make it safe : how to make it safe to talk about almost anything -- Master my stories : how to stay in dialogue when you're angry, scared, or hurt -- State my path : how to speak persuasively, not abrasively -- Explore others' paths : how to listen when others blow up or clam up -- Move to action : how to turn crucial conversations into action and results -- Yeah, but : advice for tough cases -- Putting it all together : tools for preparing and learning.
Includes bibliographical references (page 31) and index.
Keywords: Interpersonal communication; Interpersonal relations; Communication; Interpersonal Relations